Crime does not pay ; The CP Lopez story ; The Sariwang musika ni Joey Ayala [videorecording] - Lazaro, Cheche; Valdes, Luchi Cruz (Probe Productions, 1991)
Crime does not pay deals with the interview of arrested kidnappers. The second part is about the kidnapping and killing of CP Lopez, a DLSU student from Bacolod. Sariwang Musika is about Joey Ayala and his music.